"I Just Don'T Get it": Perceived Artists' Intentions Affect Art Evaluations. (July 2014) - Jucker, Jean-Luc; Barrett, Justin L.; Wlodarski, Rafael
Cognitive approaches have recently been proposed for understanding art appreciation, emphasizing the role of perceived artist's intentions and messages in how lay people define what is "art" and what is "good" art. In particular, it is argued that a work of art automatically triggers speculation about the artist's intention, and that it is intuitively assessed as an act of symbolic communication. The current experimental study tested these claims by presenting participants with various artifacts and works of art, alongside differing levels of information regarding the artist's intentions, and asking them to rate the artifacts on artistic merit. In total, 505 adults participated in four experiments. In experiment 1, participants used the artists' putative intentions to decide whether certain artifacts were instances of "art." In experiments 2a and 2b, titles that ostensibly clarified the artists' messages were found to increase participants' understanding and, importantly, liking of a series of works of art. In experiment 3, high levels of perceived investment from artists were found to increase how much participants liked a series of paintings. Overall, the results suggest that perceived artists' intentions and messages affect what people consider to be art and good art. The art experience is not only about beauty or hedonistic pleasure, but involves assessment of the artist's intention and of the history behind the work of art.